INTEGRATING ESG INTO SUSTAINABLE HRM: DIRECTED CONTENT ANALYSIS OF INDONESIAN SUSTAINABILITY REPORTS - Hernanda Alfioni; Riza Aryanto (Universitas Tulungagung, 2026)
The development of sustainability reporting in Indonesia currently does not guarantee the integration of ESG commitments into human resource management (HRM) systems. To address this issue, this study constructs and validates a new instrument to measure the maturity of ESG-HRM integration while mapping its primary gaps. The evaluation protocol assesses five domains of sustainability standards across 20 corporate sustainability reports using a double-coding scheme based on a structured codebook. Subsequently, the study employs nonparametric tests to compare the scores across domains before mapping corporate positions onto a four-quadrant matrix. The empirical results indicate that companies prioritize the disclosure of ESG commitments over their practical implementation within the HRM domain. Specifically, the scarcity of performance metrics and incentives triggers this critical integration gap. Meanwhile, governance and occupational safety disclosures display a relatively advanced level of maturity. Theoretically, these findings enrich the discourse on decoupling and institutional theories by localizing compliance gaps within a specific HR subsystem. Practically, this instrument provides a robust diagnostic tool for regulators and investors to distinguish substantive integration from administrative compliance, evaluating sustainability reporting quality and positioning remuneration system reform as the primary strategic lever.